Cellular and molecular mechanisms of glioblastoma malignancy: Implications in resistance and therapeutic strategies. (October 2019) - Balça-Silva, Joana; Matias, Diana; Carmo, Anália do; Sarmento-Ribeiro, Ana Bela; Lopes, Maria Celeste; Moura-Neto, Vivaldo
Abstract: Glioblastoma (GB) is the more frequent and malignant brain tumour. In spite of all efforts, the median overall survival of GB patients remains approximately 15 months under therapy. The molecular biology underlying GB is complex, which highlight the need of specific treatment strategies. In fact, the deregulation of several molecular signalling pathways, the existence of the blood-brain barrier (BBB), that makes almost all the chemotherapeutic agents inaccessible to the tumour site, and the existence of a population of stem-like cells known to be responsible for tumour recurrence after therapy, can contribute to GB chemoresistance. In the present review, we summarize the reliable factors responsible for the failure of the most important chemotherapeutic agents in GB. Specifically, we describe the utmost important characteristics of the BBB, as well as the genetic, molecular and transcription factors alterations that lead to tumour malignancy, and ultimately their impact on stem-like cell plasticity modulation. Recently, nanocarriers have attracted increasing attention in brain- and tumour-targeted drug-delivery systems, owing to their potential ability to target cell surface specific molecules and to cross the BBB delivering the drug specifically to the tumour cells, improving efficacy and thus reducing non-specific toxicity. In this sense, we will lastly highlight the therapeutic challenges and improvements regarding GB treatment.